2017
DOI: 10.1371/journal.pone.0180918
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acupuncture on hot flush and menopause symptoms in breast cancer- A systematic review and meta-analysis

Abstract: BackgroundMany breast cancer patients suffer from hot flush and medical menopause as side effects of treatment. Some patients undergo acupuncture, rather than hormone therapy, to relieve these symptoms, but the efficacy of acupuncture is uncertain. This meta-analysis evaluated the efficacy of acupuncture on hot flush and menopause symptoms in women with breast cancer.MethodsA literature search was performed, following the PRISMA Statement and without language restrictions, of 7 databases from inception through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(40 citation statements)
references
References 60 publications
2
38
0
Order By: Relevance
“…Further, acupuncture may alleviate co-morbid anxiety symptoms in people with obesity [23,32,33]. Given that acupuncture is a relatively safe treatment [34][35][36] and may have additional benefits in women with BC including relief of chemotherapyinduced peripheral neuropathy [37], aromatase-inhibitor induced arthralgia [38,39], menopausal symptoms [40] and lymphoedema [41], it may represent a useful adjunctive therapy that can assist women in managing a number of bothersome symptoms and manage weight. To the best of our knowledge, there are no studies examining the effectiveness of acupuncture for weight loss in women with BC, and such research appears warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Further, acupuncture may alleviate co-morbid anxiety symptoms in people with obesity [23,32,33]. Given that acupuncture is a relatively safe treatment [34][35][36] and may have additional benefits in women with BC including relief of chemotherapyinduced peripheral neuropathy [37], aromatase-inhibitor induced arthralgia [38,39], menopausal symptoms [40] and lymphoedema [41], it may represent a useful adjunctive therapy that can assist women in managing a number of bothersome symptoms and manage weight. To the best of our knowledge, there are no studies examining the effectiveness of acupuncture for weight loss in women with BC, and such research appears warranted.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, modern Western medicine has investigated the mechanism of acupuncture based on changes in neurological, physiological, and hormonal neuronal activities. [ 99 ] Some studies show that acupuncture increases endorphin activity. Therefore, it modulates thermoregulation in the hypothalamus and neutralizes temperature in patients with vasomotor syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…[ 143 ] Another branch of complementary and alternative medicine is acupuncture. [ 99 ] Acupuncture is used to treat menopausal symptoms as a complementary and alternative therapy without serious side effects. [ 113 ] We examined 18 acupuncture studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews have suggested that adjunct CAM therapies, including acupuncture, pharmacopuncture, and herbs, have benificial effects on cancer-related symptoms, conventional treatment-associated side effects, and the response rate of the tumor. [ 27 34 ] However, limited cohort evidence has been published on its effects on survival and quality of life for patients being treated with TKM. The objective of this prospective cohort study is to evaluate both the effect of ACTKMT on EFS, DFS/PFS, OS, quality of life, blood test results, and telomere length and the adverse events associated with ACTKMT.…”
Section: Discussionmentioning
confidence: 99%